2019
DOI: 10.14334/wartazoa.v29i4.2452
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Increasing Beef Cattle Production under Dryland Farming Systems

Abstract: Integrated cattle and dryland farming systems in Indonesia use a range of crop residues and by products to feed cattle through intensive and extensive production systems. Intensive systems use stalls to house cattle and cut and carry feeding systems, primarily for fattening cattle. Under extensive systems, cattle are free‐grazing,and the systems apply only where greater land areas exist and they are used for breeding and fattening cattle. This paper therefore specifically focuses on the opportunities that exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
7
0
3
Order By: Relevance
“…Therefore, a shift in management and receptivity to development interventions should be prioritized. A report on Indonesian beef cattle by [ 52 ], suggested that cost-effective interventions such as a defined breeding calendar, suckling restriction period, and pre and post-calving nutrition should be implemented for fertility improvement. A breeding calendar that is in concurrence with the rainy season is of most importance and can assist balance peak nutritional demands with the provision of enough grazing pasture preferably at late pregnancy and early lactation to promote re-conception [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a shift in management and receptivity to development interventions should be prioritized. A report on Indonesian beef cattle by [ 52 ], suggested that cost-effective interventions such as a defined breeding calendar, suckling restriction period, and pre and post-calving nutrition should be implemented for fertility improvement. A breeding calendar that is in concurrence with the rainy season is of most importance and can assist balance peak nutritional demands with the provision of enough grazing pasture preferably at late pregnancy and early lactation to promote re-conception [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Feed is a source of energy for livestock growth, hence, the better the quality and the sufficient quantity, the greater the energy stored in the form of meat (Prabowo et al, 2008). Similar to a business, the time of effort is one of the determinants of obtaining optimal profits by accelerating cattle growth, increasing reproduction, and reducing mortality (Burrow, 2019). Feed improvement simulations with the addition of concentrate were carried out on the fattening sub-model to increase the appearance of cow production with the ratio of grass and concentrates of 30%: 70%.…”
Section: Productivitymentioning
confidence: 99%
“…Penerapan teknologi budidaya ternak ditujukan untuk pengembangan populasi dan produktivitas ternak (Burrow, 2019). Pengembangan populasi diarahkan dengan implementasi teknologi inseminasi buatan.…”
Section: Pendahuluanunclassified